2022
DOI: 10.1111/jcpe.13594
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional ridge changes in conjunction with four implant timing protocols and two types of soft tissue grafts: A pilot pre‐clinical study

Abstract: Aim: To determine the effect of (1) implant placement timing and (2) the type of soft tissue graft in terms of ridge profile changes.Materials and Methods: Four implant treatment modalities were applied in the mesial root areas of the third and fourth mandibular premolars of 10 mongrel dogs alongside connective-tissue graft (CTG) and volume-stable cross-linked collagen matrix (VCMX): immediate, early, and delayed placement (DP), and DP following alveolar ridge preservation (ARP). All dogs were sacrificed 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…That thickness was comparable to the values in the groups with CTG other than group IP/CTG. Our primary study using STL analyses had shown a similar trend (Lee et al, 2022). The linear tissue gain was also largest in group EP/VCMX.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…That thickness was comparable to the values in the groups with CTG other than group IP/CTG. Our primary study using STL analyses had shown a similar trend (Lee et al, 2022). The linear tissue gain was also largest in group EP/VCMX.…”
Section: Discussionsupporting
confidence: 68%
“…The present study found that CTG tended to result in larger overall and soft‐tissue thicknesses in all implant placement protocols compared with VCMX, despite our primary STL analyses revealing that both CTG and VCMX enhanced the overall tissue contour (Lee et al, 2022). This indicates that clinicians should be careful in case selection in their decision making about using an autogenous soft‐tissue transplant or a soft‐tissue substitute material (Cosyn et al, 2022).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…To overcome these drawbacks, several collagen-based matrices have been developed and evaluated in both clinical and preclinical settings. Although these collagen matrices have demonstrated promising results, their performance generally has not exceeded, or has even been inferior to, that of SCTG in terms of soft tissue volume gain [ 10 11 12 ]. Furthermore, significant volume shrinkage has been observed over time at sites treated with collagen matrix.…”
Section: Introductionmentioning
confidence: 99%